2021
DOI: 10.1521/pedi_2021_35_519
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effectiveness and Predicting Outcome and Dropout From Systems Training for Emotional Predictability and Problem Solving for Emotional Intensity Difficulties (STEPPS EI) in UK Primary Care

Abstract: Systems Training for Emotional Predictability and Problem Solving (STEPPS) for borderline personality disorder (BPD) has been adapted for a primary care setting into a 13-week group treatment for emotional intensity difficulties (STEPPS EI). This is the first study to examine the effectiveness and potential outcome and dropout predictors of STEPPS EI in a primary care setting. Severity of BPD, depression, and anxiety symptoms were measured pre- and postintervention for 148 participants. Treatment completers sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Three RCTs have been performed on STEPPS (Blum et al, 2008; Bos et al, 2010; Bos et al, 2011), with all three reporting follow‐up data. Eleven (uncontrolled) pretreatment versus posttreatment research designs were found (Alesiani et al, 2014; Black et al, 2008, 2013; Blum et al, 2002; Boccalon et al, 2017; González‐González et al, 2021; Guillén et al, 2021; Harvey et al, 2010; Hezelyova et al, 2021; Hill et al, 2016; Llorens Ruiz et al, 2020). One study compared STEPPS with another form of psychotherapy (i.e., DBT; Guillén Botella et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three RCTs have been performed on STEPPS (Blum et al, 2008; Bos et al, 2010; Bos et al, 2011), with all three reporting follow‐up data. Eleven (uncontrolled) pretreatment versus posttreatment research designs were found (Alesiani et al, 2014; Black et al, 2008, 2013; Blum et al, 2002; Boccalon et al, 2017; González‐González et al, 2021; Guillén et al, 2021; Harvey et al, 2010; Hezelyova et al, 2021; Hill et al, 2016; Llorens Ruiz et al, 2020). One study compared STEPPS with another form of psychotherapy (i.e., DBT; Guillén Botella et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Baseline characteristics, such as gender, age, and ethnicity, were not associated with greater improvement after treatment (Black et al, 2018a). Nonetheless, higher educational level, better patient collaboration, higher baseline symptom severity, and absence of a bipolar disorder did predict better outcome (González‐González et al, 2021; Hezelyova et al, 2021). Analyses of dropouts demonstrate no significant differences in sex, school level, and DSM diagnoses between dropouts and completers (Alesiani et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation